2012
DOI: 10.4100/jhse.2012.74.04
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of race pace in long distance running from blood lactate concentration around race pace

Abstract: Muñoz-Pérez I, Moreno-Pérez D, Cardona-González C, Esteve-Lanao J. Prediction of race pace in long distance running from blood lactate concentration around race pace. J. Hum. Sport Exerc. Vol. 7, No. 4, pp. 763-769, 2012. The aim of this study was to develop an equation for predicting the performance in 10 kilometers road race (10k), Half Marathon (21k) and Marathon (42k), using the blood lactate concentration (bLA) close to race pace. 64 runners of different levels completed the study (10k (n = 19): 32min-56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The main strength of this study is the comparison of prediction models in which the v VO 2 max is found as the most frequently variable related to performance in runners (Morgan et al, 1989; Noakes et al, 1990; Muñoz et al, 2012) and an easy-to-perform field test in a training schedule.…”
Section: Discussionmentioning
confidence: 99%
“…The main strength of this study is the comparison of prediction models in which the v VO 2 max is found as the most frequently variable related to performance in runners (Morgan et al, 1989; Noakes et al, 1990; Muñoz et al, 2012) and an easy-to-perform field test in a training schedule.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the abovementioned correlation studies, an approach to study determinants of performance in HM is to develop prediction equations of race time based on correlates (Pérez et al 2012;Gómez-Molina et al 2017), which include usually two steps, first, the development of an equation in a sample of runners, and second, the validation of this equation in another sample. For instance, a study on runners considered training-related and anthropometric variables, and laboratory data from a graded exercise test (GXT) on a treadmill (VO 2 max, speed at the anaerobic threshold, peak speed) and biomechanical variables (contact and flight times, step length and step rate) (Gómez-Molina et al 2017).…”
Section: Physiological Correlates Of Performancementioning
confidence: 99%
“…This study found that HM race time could be predicted to 90.3% by variables related to training and anthropometry, 94.9% by physiological variables, 93.7% by biomechanical parameters and 96.2% by a general equation, and using these equations, the predicted time was significantly correlated with performance (r = 0.78, 0.92, 0.90 and 0.95, respectively) (Gómez-Molina et al 2017). Moreover, HM race speed could be predicted as V21k (km/h) = (V2*1.085) + (− −0.131, r2 = 0.97, ETE = 0.414 km/h, where V2 was the speed during a test in track at constant pace over 2400 m slightly higher than the competition expected pace and bLA2 blood lactate (Pérez et al 2012). A research examined the ratio between running speed and heart rate (HR) as predictor for aerobic capacity (based on the assumption that lower HR at a given speed is expected for more fit individuals), and subsequently race time in 10 km, HM and FM (Altini et al 2017).…”
Section: Physiological Correlates Of Performancementioning
confidence: 99%
“…In performance diagnostics, blood lactate (LA) concentrations are frequently used to determine endurance capacity (Broich et al, 2012;Goodwin et al, 2007), to give specific training recommendations (Stegmann et al, 1981) and to predict athletic performance in competitions (Muñoz Perez et al, 2012). Skeletal muscle produces and releases large amounts of LA during high intensity exercise.…”
Section: Introductionmentioning
confidence: 99%